(untitled) (Research, Society and Development, 2021)
Chronic kidney disease – CKD is defined as a slow, progressive and irreversible decrease in kidney function. There are several treatment options, including hemodialysis, the subject of this study; patients undergoing hemodialysis have changes in their nutritional status such as deficiency in systemic blood pressure control mechanisms, anemia due to reduced production of EPO (erythropoietin), reduction in the final activation of vitamin D with consequent bone disease, mostly due to excess PTH (parathormone), which removes calcium from the bone to maintain serum levels of this ion, in addition to the accumulation of substances in the blood that should be eliminated in the urine (characterizing uremia), depression and malnutrition that in itself contributes to for the morbid state easily seen in renal patients.